Othering Older People's Housing: Gaming Ageing to Support Future-Planning. - McCall,V; Rutherford,AC; Bowes,A; Jagannath,S; Njoki,M; Quirke,M; Pemble,CM; Lovatt,M; Davison,L; Maginn,K; Scrutton,P; Pengelly,R; et al. (Int J Environ Res Public Health, 2024)
The 'othering' of ageing is linked to an integrated process of ageism and hinders planning for the future for both individuals and practitioners delivering housing and health services. This paper aims to explore how creative interventions can help personalise, exchange knowledge and lead to system changes that tackle the 'othering' of ageing. The Designing Homes for Healthy Cognitive Ageing (DesHCA) project offers new and creative insights through an innovative methodology utilising 'serious games' with a co-produced tool called 'Our House' that provides insights into how to deliver housing for older people for ageing well in place. In a series of playtests with over 128 people throughout the UK, the findings show that serious games allow interaction, integration and understanding of how ageing affects people professionally and personally. The empirical evidence highlights that the game mechanisms allowed for a more in-depth and nuanced consideration of ageing in a safe and creative environment. These interactions and discussions enable individuals to personalise and project insights to combat the 'othering' of ageing. However, the solutions are restrained as overcoming the consequences of ageism is a societal challenge with multilayered solutions. The paper concludes that serious gaming encourages people to think differently about the concept of healthy ageing-both physically and cognitively-with the consideration of scalable and creative solutions to prepare for ageing in place.